2001
DOI: 10.1135/cccc20010185
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Molecular Electrochemistry of Metallocene Dichloride and Dimethyl Complexes of Group 4 Metals: Redox Properties and Relation with Optical Ligand-to-Metal Charge Transfer Transitions

Abstract: Emphasis is given to redox, photophysical, and photochemical properties of homologous bent metallocenes of group 4 transition metals. Comparative analysis of a variety of electron-transfer induced transformations and ligand-to-metal charge-transfer excited states is performed for bent metallocene complexes upon systematic variation of the identity of the metal ion (Ti, Zr or Hf), ancillary π- and monodentate σ- (Cl, Me) ligands. For such organometallic π-complexes, linear correlations exist between energies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 116 publications
(135 reference statements)
0
25
0
Order By: Relevance
“…However, solvent effects and transitions involving the SHOMO and SLUMO (and potentially other MOs), as well as changes in relative orbital energies and electron configurations, can significantly complicate the situation to the extent that one can generally only get meaningful information by comparing closely related compounds [25,26]. Although group 4 half-sandwich complexes have been investigated by cyclic voltammetry and UV/visible spectroscopy [26][27][28][29], the processes and orbitals involved are quite different from those observed in diindenyl ferrocene systems: Firstly, oxidation of the group 4 complexes occurs from ligand-based orbitals rather than metal-based d orbitals [26,29,30], and, secondly, although the UV/visible spectroscopy provides information on the HOMO-LUMO gap in both systems, it is an LMCT process from the indenyl to a d 0 metal centre in the group 4 complexes [26,27,29] rather than a d-d transition of the d 6 Fe atom [19,31]. One must be careful, therefore, when making comparisons between these systems.…”
Section: Resultsmentioning
confidence: 99%
“…However, solvent effects and transitions involving the SHOMO and SLUMO (and potentially other MOs), as well as changes in relative orbital energies and electron configurations, can significantly complicate the situation to the extent that one can generally only get meaningful information by comparing closely related compounds [25,26]. Although group 4 half-sandwich complexes have been investigated by cyclic voltammetry and UV/visible spectroscopy [26][27][28][29], the processes and orbitals involved are quite different from those observed in diindenyl ferrocene systems: Firstly, oxidation of the group 4 complexes occurs from ligand-based orbitals rather than metal-based d orbitals [26,29,30], and, secondly, although the UV/visible spectroscopy provides information on the HOMO-LUMO gap in both systems, it is an LMCT process from the indenyl to a d 0 metal centre in the group 4 complexes [26,27,29] rather than a d-d transition of the d 6 Fe atom [19,31]. One must be careful, therefore, when making comparisons between these systems.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, it was demonstrated that the same MOs are involved in both optical and redox electron transfer in these metallocenes [2,[5][6][7].…”
mentioning
confidence: 98%
“…Experimental study of the properties of organometallic compounds of early transition metals [2,3] and their shortlived intermediates (catalysis [4], redox processes [5], including free radical ones, etc.) is a difficult task.…”
mentioning
confidence: 99%
“…The long lived excited state of complex 1 is formed due to the ligand to metal charge transfer, which is rarely observed in the photophysics of organometallic compounds. [10][11][12] Solutions of single crystals were studied. All solvents used were multiply purified from traces of impurities, oxy gen, and moisture and subjected to freezing-thawing out cycles using known procedures.…”
mentioning
confidence: 99%